TINJAUAN HUKUM PENTINGNYA FASILITAS KONSUMEN DI SUPERMARKET (TRANSMART) - Muh Asyhari (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Sunan Gunung Djati Bandung, 2021)
In building a place, many things need to be considered, one of which is facilities. In order to create comfort for consumers. Places that have supporting facilities will have a positive impact on consumers, but conversely if the facilities provided are less than the maximum it will have a negative impact. In supermarkets, consumers will return to shop at the place when the services provided are good. Generally the facilities that are most often considered are clean and neat toilets, a well organized parking lot, for Muslims, one of the important things is the availability of a clean and comfortable prayer room for worship. All of that are consumer rights that must be fulfilled by the manager, but there are also consumer obligations that must be fulfilled so that no party feels disadvantaged.Keywords: facilities, Muslims, service, satisfaction